PERKEMBANGAN PERANAN BIOTEKNOLOGI PADA TANAMAN TRANSGENIK DI DUNIA DAN INDONESIA - Susanto, Susanto; Apdillah, Zaka; Gunawan, Ahmad; Tanjung, Dicky Zulkarnain (Fakultas Pertanian, Universitas Janabadra, 2024)
Indonesia has a very rich biodiversity, is an important raw material for the development of modern biotechnology (DNA technology), this container material is used as a source of new genes to increase the productivity of the agricultural industry. Transgenic plants developed in Indonesia and used as food and feed such as corn, soybeans and potatoes must meet biosafety requirements. The research used is qualitative research. The type of research used in this study is descriptive research. Transgenic plant production The production of transgenic plants involves several steps in molecular biological engineering. The desired properties must be selected and the genes that control the gene must be identified. In the 18 years since this commercial crop began to grow, the crop area has increased 100 times, from just 1.7 million ha in 1996 to 175.2 million hectares in 2013. The total of transgenic crops in Latin America, Asia and Africa is 94 million hectares or 54% of the world's 175.2 million transgene crops, compared to 81 million hectars or 46% in the industrialized countries. This technology can be applied on condition: the application of transgenic crops in the field requires management that can regulate patterns of cultivation of transgene and non-transgene crops, the provision of controlled transgene seedlings in the form of seed packages, the need for legal certainty, government support for transgene products, and a routine evaluation of the implementation of Transgenic plant technology. Keywords : Biotechnology, Agriculture, Production, Transgenic INTISARIIndonesia memiliki keanekaragaman hayati yang sangat kaya, merupakan bahan baku penting untuk pengembangan bioteknologi modern (teknologi DNA), bahan baku ini digunakan sebagai sumber gen baru untuk meningkatkan produktivitas industri pertanian. Tanaman transgenik yang dikembangkan di Indonesia dan digunakan sebagai bahan pangan dan pakan seperti jagung, kedelai dan kentang harus memenuhi persyaratan biosafety. Penelitian yang digunakan adalah penelitian kualitatif. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian deskriptif. Produksi Tanaman Transgenik Produksi tanaman transgenik melibatkan beberapa langkah dalam teknik biologi molekuler. Sifat yang diinginkan harus dipilih dan gen yang mengendalikan gen tersebut harus diidentifikasi. Perkembangan tanaman transgenik dunia Dalam 18 tahun sejak budidaya komersial tanaman ini dimulai, luas tanam telah meningkat 100 kali lipat, dari hanya 1,7 juta hektar pada tahun 1996 menjadi 175,2 juta hektar pada tahun 2013. Luas total tanaman transgenik di Amerika Latin, Asia dan Afrika adalah 94 juta hektar atau 54% dari 175,2 juta tanaman transgenik dunia, dibandingkan dengan 81 juta hektar atau 46% di negara industri . Solusi Untuk Tanaman Transgenik di Indonesia Teknologi ini dapat diterapkan dengan syarat: aplikasi tanaman transgenik di lapangan perlu manajemen yang dapat mengatur pola tanam tanaman transgenik dan non transgenik, penyediaan bibit tanaman transgenik dikendalikan dalam bentuk paket kemasanbenih, perlunya kepastian hukum,dukungan pemerintah terhadap produk transgenik, dan evaluasi rutin terhadap penerapan teknologi tanaman transgenik. Kata kunci : Bioteknologi, Pertanian, Produksi, Transgenik